2019
DOI: 10.21776/ub.jtsl.2019.006.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Biochar Serbuk Kayu Durian Terhadap Karakteristik Tanah Sulfat Masam Dalam Mengurangi Emisi Gas Metana

Abstract: Organic matter in the soil can provide nutrients to plants. The objectives of this study were to analyze soil characteristics after incubation using biochar at various doses, and to calculate the reduction of methane gas emissions from incubated soils. The treatments were (1) soil control (T0);(2) 4 t ha -1 biochar + soil (T1); (3) 8 t ha -1 biochar + soil (T2); (4) 12 t ha -1 biochar + soil (T3); (5) 16 t ha -1 biochar + soil (T4); (6) 20 t ha -1 biochar + soil (T5). The soil of each treatment was incubated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…The role of organic acids both from water hyacinth compost (H1) and from manufactured humic (H2) is to maintain a reductive atmosphere and can chelate metals such as Fe 3+ [41]. Research of [42], showed that adding organic matter (4,8,12,16, and 20 tons/ha) and an incubation time of 30 days could suppress pyrite oxidation and increase soil pH from 3.73 to 5.38. The Addition of organic matter can suppress the occurrence of pyrite oxidation caused by Fe 3+ ions by reducing the rate of Fe 3+ production in the Fe 3+ reduction process to Fe 2+ and increasing oxygen consumption by decomposer microorganisms and can cover the pyrite layer so that it does not come into direct contact with oxygen [43].…”
Section: Figure 2 Properties Of Soil Due To the Treatment Of Soil Ame...mentioning
confidence: 99%
“…The role of organic acids both from water hyacinth compost (H1) and from manufactured humic (H2) is to maintain a reductive atmosphere and can chelate metals such as Fe 3+ [41]. Research of [42], showed that adding organic matter (4,8,12,16, and 20 tons/ha) and an incubation time of 30 days could suppress pyrite oxidation and increase soil pH from 3.73 to 5.38. The Addition of organic matter can suppress the occurrence of pyrite oxidation caused by Fe 3+ ions by reducing the rate of Fe 3+ production in the Fe 3+ reduction process to Fe 2+ and increasing oxygen consumption by decomposer microorganisms and can cover the pyrite layer so that it does not come into direct contact with oxygen [43].…”
Section: Figure 2 Properties Of Soil Due To the Treatment Of Soil Ame...mentioning
confidence: 99%
“…Menurut penelitian Setiawati et al (2019), penurunan pH dapat terjadi seiring dengan peningkatan waktu inkubasi. Kemudian pada hari ke-10 hingga ke-25, pH tanah tidak mengalami perubahan.…”
Section: Pengaruh Penambahan Biochar Terhadap Ph Tanahunclassified